Review on technical aspects of image acquisition, analysis and retrieval for leukaemia cells - Rajendran, S.; Arof, Hamzah; Ibrahim, Fatimah; Yegappan, S. (2008)
This paper reviews the technical aspects of the state-of-art techniques and procedures for image acquisition, pre-processing, image processing and analysis, search and retrieval techniques for leukaemia blood cell images. Hospital Ampang gets a fair amount of leukaemia cases every year but the hematology department of Hospital Ampang lacks the digital format of patient management system and leukaemia images storage and retrieval system. So, a survey on technical aspects of acquisition, analysis and retrieval was conducted to propose and develop patient management system and leukaemia diagnosis support system for Hospital Ampang, Malaysia. Â© 2008 Springer-Verlag.